2015
DOI: 10.1002/cnma.201500014
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole‐Based Molecular Glasses as Hole‐Transporting Materials in Solid State Dye‐Sensitized Solar Cells

Abstract: Three 3,6-di(4-methoxyphenyl)amino N-alkylated carbazoles were synthesized, characterizeda nd incorporated in solid state dye-sensitized solar cells. Devices using these compoundsa ss olid hole conductors showedr elative high V oc thanks to good energy level matching betweent hem and D102 dye. However,t hey yield relativelyl ow J sc and FF compared to spiro-OMeTAD-based control devices, which is due to an order of magnitude lower mobility and conductivity with respect to spiro-OMeTAD. Maximum PCEs for Nethyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…In this phase, the contacts between the HTM and the sensitizer are maximized,thus increasing the charge transport and and hence the performance of the ssDSSC. [13][14][15] Following Eq.2, high hopping rates and high charge carrier mobility require a low value of λ while transport integrals J ij must be high. Tab.4 reports the values of the hole and electron reorganization energies.…”
Section: Charge Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this phase, the contacts between the HTM and the sensitizer are maximized,thus increasing the charge transport and and hence the performance of the ssDSSC. [13][14][15] Following Eq.2, high hopping rates and high charge carrier mobility require a low value of λ while transport integrals J ij must be high. Tab.4 reports the values of the hole and electron reorganization energies.…”
Section: Charge Transport Propertiesmentioning
confidence: 99%
“…Bui et al fabricated carbazole-based HTMs with high solubility, low molar weight 3 and able to operate in the amorphous phase. [13][14][15] Song et al 16 and Lv et al 17 designed novel small HTMs synthesizable with a simple low-cost process obtaining high device performances.…”
Section: Introductionmentioning
confidence: 99%
“…A second comparison can be made between the work of Degbia et al and that of Bui et al, as they both reported devices fabricated with the same dye and hole conductor, named 1 255 and 2a, 256 respectively. This compound is similar to 3b and X19 but it features an ethyl group attached to the nitrogen of the carbazole instead of a p-methoxyphenyl one.…”
Section: Organic Hole Transporting Materialsmentioning
confidence: 99%
“…On the other hand, molecular HTMs are beneficial in terms of synthetic reproducibility and well‐defined molecular weight and structure. Among the various organic HTMs that have been developed, our interest has focused on arylamine derivatives, which offer interesting electrochemical properties, good charge‐transport properties, and high thermal and morphological stabilities . Among these compounds, a number of simple donor−π−donor molecular HTMs have been synthetized by varying the central π linker and the end‐capping arylamine derivatives .…”
Section: Introductionmentioning
confidence: 99%